Single-Cell Transcriptomics of Immune Cells Reveal Diversity and Exhaustion Signatures in Non-Small-Cell Lung Cancer - Zhao, Ying; Zhang, Qilin; Tu, Kailin; Chen, Yanmei; Peng, Yuxuan; Ni, Yinyun; Zhu, Guonian; Cheng, Cheng; Li, Yangqian; Xiao, Xue; Yu, Chunyan; Lu, Keying; et al. (Frontiers in Immunology, 2022)
Understanding immune cell phenotypes in the tumor microenvironment (TME) is essential for explaining and predicting progression of non-small cell lung cancer (NSCLC) and its response to immunotherapy. Here we describe the single-cell transcriptomics of CD45+ immune cells from tumors, normal tissues and blood of NSCLC patients. We identified three clusters of immune cells exerting immunosuppressive effects: CD8+ T cells with exhausted phenotype, tumor-associated macrophages (TAMs) with a pro-inflammatory M2 phenotype, and regulatory B cells (B regs) with tumor-promoting characteristics. We identified genes that may be mediating T cell phenotypes, including the transcription factors ONECUT2 and ETV4 in exhausted CD8+ T cells, TIGIT and CTL4 high expression in regulatory T cells. Our results highlight the heterogeneity of CD45+ immune cells in the TME and provide testable hypotheses about the cell types and genes that define the TME.